EVALUATING CMS PAYMENT REFORM INITIATIVE TO REDUCE AVOIDABLE HOSPITALIZATIONS AMONG NURSING FACILITY RESIDENTS. (11th November 2018) - Ingber, M; Gaines, J
Abstract: Nursing home residents are characterized by frailty, multiple chronic illnesses, and high levels of physical and cognitive impairment. More than one-quarter of long-stay nursing home residents are hospitalized each year. These hospitalizations are costly, and many are considered potentially avoidable. Unnecessary hospitalizations cause disruption to residents, risk of complications, and possibility of reduced functioning on return to the nursing home. Reducing avoidable hospitalizations of nursing home residents is an important quality-improvement initiative that may also reduce cost of care. This symposium will include an overview of the Centers for Medicare & Medicaid Services (CMS) Initiative to Reduce Avoidable Hospitalizations among Nursing Facility Residents—Payment Reform (henceforth, the Initiative), and will describe the evaluation design and early findings. The Initiative, begun in 2016, tests a new Medicare Part B payment model that pays participating nursing facilities and practitioners for providing higher-level care on site to eligible long-stay residents instead of transferring them to hospitals. These payments are for care of residents with six qualifying conditions whose changing symptoms could possibly trigger a hospital transfer. Four presentations will focus on: (1) Description of the Initiative and individual state models, (2) An overview of evaluation methods, describing the approach to comparison group selection and quantitative impact analysis; (3) Early primary data (telephone interview) results from the perspective of participating nursing facilities; and (4) Preliminary primary data results concerning participating practitioners (physicians and physician extenders).